A song for each moment: Identifying listening modes as reflexive practices in music streaming - Sebastian Cole (Big Data & Society)
In addition to personal and contextual reasons for listening to music, users of music streaming services also receive constant recommendations from these platforms’ algorithmic systems. In this article, I explore, from a critical realist perspective, how users reflect on and decide what to listen to in various contexts. First, the article develops a framework for understanding reflexive decision-making in the context of music streaming. Then, based on interviews with Spotify users and an analysis of their donated streaming histories, three listening modes are identified based on what motivates music choices and how the users interact with the platform's content. Findings suggest that in addition to the platform's recommendations, users reflexively choose music to fit their contexts, emotions and goals based on their previous experiences, striking a balance between conscious and habitual music listening.